Determinan Partisipasi Lansia pada Program Posyandu Lansia di Kabupaten Banjarnegara - Anisa Prabaningrum; Intan Zainafree (Dian Nuswantoro Semarang, 2021)
Background: Government seeks health services for the elderly by holding the Elderly Posyandu. Gelang urban village 3th hamlet is working area of Rakit 1 Health Center which has a decreased percentage of elderly visits, namely 25.75% in September and 16.5% in October. This is due to the physical condition of the elderly and the concern of the elderly when the disease is revealed. The purpose of this study was to determine the participation of elderly and factors supporting and inhibiting. Methods: research method uses a qualitative approach with purposive sampling technique. Data were collected by observation, documentation, and in-depth interviews with 7 peoples. To prove the validity of the data using triangulation techniques to 5 people. Results: form of elderly participation is social participation, existence of proposals, and the provision of voluntary cash. The percentage elderly visits showed only 10.62%. This is because of positive response from elderly, as gathering place, existence gymnastics activities, distance and friendly service. The inhibiting factors are physical condition, the busyness, fear, incomplete infrastructure, lack of family support, existence of screening, and forget about the schedule of activities. Conclusion: participation still low so efforts are needed community leaders to overcome the inhibiting factors to increase elderly visits. Keywords: Participation, Inhibiting, Supporting, Utilization of Posyandu